Craniocervical Instability in the Setting of Os Odontoideum: Assessment of Cause, Presentation, and Surgical Outcomes in a Series of 279 Cases. Issue 5 (May 2015) - Zhao, Deng; Wang, Shenglin; Passias, Peter G.; Wang, Chao
Abstract : BACKGROUND: Our clinical understanding of os odontoideum (OO) remains incomplete. Congenital and traumatic causes have been proposed and advocated. Clinical presentations range from asymptomatic to axial pain to myelopathy or vertebral-basilar ischemia. A consensus for surgical management exists for those found to have an unstable atlantoaxial complex or symptomatic cranial-vertebral junction compression. OBJECTIVE: To evaluate the clinical presentation and surgical outcomes of patients with OO and an unstable atlantoaxial complex or symptomatic cranial-vertebral junction compression. METHODS: Patients with a diagnosis of OO who underwent surgical management were included. Patients were excluded on the basis of previous C2 fracture, Fielding diagnostic criteria, and inadequate follow-up. History of trauma and presenting symptoms were assessed. Clinical and neurological improvements were measured with the use of patient satisfaction scores and the Japanese Orthopaedic Association scores. Fusion status was documented with the use of radiographs and computed tomographic imaging. RESULTS: Of 279 patients, 112 reported a history of cranial-vertebral junction trauma, whereas 28 were diagnosed with congenital malformations. Clinically, 84.9% of patients presented with myelopathy, with pain presented in 42.6%. Atlantoaxial fixation was performed in 240 patients, occiput-to-C2 fixation in 35 patients, and extended occipito-cervical fixation in 4 patients. Mean follow-up was 40.3 months. Complications were reported in 2.4% of patients. Japanese Orthopaedic Association scores improved from a preoperative mean of 12.4 to 14.8. Two hundred thirty-five patients (77.7%) improved, with 30 patients experiencing no change in symptoms and 14 patients deteriorating. Fusion was achieved in 96.8% of patients. CONCLUSION: Our data reveal that surgical treatment for OO using the indications and techniques delineated is associated with high satisfaction rates, improved functional scores, and high fusion rates with low complication rates. ABBREVIATIONS: AAI, atlantoaxial instability JOA, Japanese Orthopaedic Association OO, os odontoideum